Independent effects of early life adversity on social cognitive function in patients with schizophrenia - Peng, Xing; Hou, Wen-Peng; Ding, Yu-Shen; Wang, Qi; Li, Feng; Sha, Sha; Yu, Chen-Chao; Zhang, Xiu-Jun; Zhou, Fu-Chun; Wang, Chuan-Yue (Frontiers in Psychiatry, 2024)
Objective The aim of this study was to investigate the impact of early life adversity on cognitive function in patients with schizophrenia, with a focus on social cognition (SC). Methods Two groups of patients with schizophrenia were recruited and matched on sociodemographic and clinical characteristics. One group consisted of 32 patients with a history of childhood trauma (SCZ-ct), and the other group consisted of 30 patients without a history of childhood trauma (SCZ-nct). In addition, 39 healthy controls without a history of childhood trauma (HC-nct) were also recruited. The intelligence of the three groups was assessed using the Wechsler Abbreviated Scale of Intelligence (WAIS—RC) short version. The cognitive function evaluation was conducted using the MATRICS Consensus Cognitive Battery (MCCB), and early life adversity was measured using the Childhood Trauma Questionnaire-Short Form (CTQ) and Bullying Scale for Adults (BSA). Results Patients with schizophrenia endosed significantly higher scores on the CTQ (F=67.61, p<0.001) and BSA (F=9.84, p<0.001) compared to the HC-nct. Analysis of covariance (ANCOVA) and post-hoc analyses revealed that SCZ-ct (F=11.20, p<0.001) exhibited the most pronounced cognitive impairment among the three groups, as indicated in MCCB total scores and in the domain score of SC. CTQ exhibited a negative correlation with MCCB (r=-0.405, p< 0.001); SC was negatively correlated with physical abuse (PA) of CTQ (r=-0.271, p=0.030) and emotional abuse (EA) of BSA (r=-0.265, p=0.034) in the whole patient sample. Higher SC performance was significantly predicted by CT_total (Beta =-0.582, p<0.001, 95% CI -0.96-0.46), and years of education (Beta=0.260, p =0.014, 95% CI 0.20-1.75) in schizophrenia. Conclusions Besides familial trauma, schizophrenia patients appear to have a higher likelihood of experiencing bullying in their early life. These experiences seem to contribute significantly to their severe impairments in SC.